The Expression of The Symbolic Phrases "To Think" in Uzbek-Karakalpak Literary Text - Abdullayev Shukhrat Dauletbayevich; Karimova Dilnoza Otaxon qizi (International Journal on Integrated Education, 2021)
The article describes the use of semantic phrases “to think” in Uzbek and Karakalpak languages, their linguistic nature, lexical-semantic features, general and specific aspects of their structure and meaning.